The impact of resource efficiency measures on performance in small and medium-sized enterprises - Jens Horbach (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
The profitability of green investment is crucial for the diffusion of the resulting technologies but the knowledge about these effects is still limited. Positive performance effects may be based on cost savings stemming from the introduction of cleaner production processes connected with lower material and/or energy use. The present paper empirically analyzes the effects of environmentally active behavior on the performance of a firm. The analysis is based on the 2013 wave of the Eurobarometer data for small and medium-sized firms (SME's). The analysis for SME's seems to be interesting because small firms might be especially affected by the costs of environmental measures as the introduction of resource efficiency measures are costly in the short run. The results of a bivariate probit model show that a high amount in investment in resource efficiency measures triggers the overall performance of the firm. A high selfperceived greenness of the firm and a high share of green employment are positively correlated to performance. In fact, not all measures in improving resource efficiency are connected with positive performance effects: An increased use of renewables leads to a higher performance whereas measures to reduce water consumption are negatively correlated to turnover development.
Keywords: C35; O33; Q55; 330; eco-innovation; bivariate probit model; SME